Docking operation by multiple space robots for minimum attitude disturbance*. (2nd January 2018) - Dalla, Vijay Kumar; Pathak, Pushparaj Mani
Abstract: Object handling is challenging for space robots due to its free-floating base, which rotates and translates during object interaction. Hence, these consequences affect the position and the attitude disturbance due to being strongly coupled and non-holonomic space robot characteristics. The attitude disturbance can be very crucial as ground communication depends upon the spacecraft's attitude/orientation. If attitude disturbance is controlled by equipping the attitude controller in a space robot, this may shorten the space mission life through fuel consumption, as spacecraft can carry only limited fuel. This work was motivated by curiosity to see if a floating object can be handled by three space robots and whether attitude disturbance would be more or less when two space robots are used for the same act. Would handling operation by three space robots be more stable than two space robots? Simulation and animation studies were carried out to analyze the results. It was observed that docking by each manipulator of the two space robots provides more attitude disturbance than three space robots. This shows that the three space robots provide increased stability than the two space robots. The bond graph modeling methodology was used to model the system dynamics.